Association between alpha-1-acid glycoprotein and frailty in US females aged 20–49 years: analysis of NHANES data (2015–2023) - Yaru Liu; Yunxun Chen; Lijuan Zhou; Yantao Yin; Yuqiong Cao; Guang Li; Tian Xu; Xianxiu Wen (Scientific Reports)
Abstract As a significant global health issue, frailty has important implications for clinical practice and public health. Systemic inflammation has been identified as an important mechanism influencing the development of frailty. However, the potential impact of the inflammatory marker alpha-1-acid glycoprotein (AGP) on frailty is unclear. The aim of this study was to investigate the relationship between AGP levels and frailty. The present study employed a cross-sectional design and included a sample of 3802 females aged 20–49 years, drawn from the 2015–2023 National Health and Nutrition Examination Survey (NHANES) database. A weighted multivariate logistic regression was employed to construct a series of adjustment models, comprising crude, partial and fully adjusted models, with the objective of testing the potential association between AGP and frailty. Smoothed curve fitting plots were used to test the nonlinear relationship between AGP and frailty. The diagnostic value of AGP and hsCRP for frailty was compared using receiver operating characteristic (ROC) curve analysis. Finally, subgroup analyses and interaction tests were conducted to explore the stability of the findings. After adjusting for all potential confounding variables, AGP was found to be significantly and positively associated with frailty, with a corresponding 2.42-fold increase in the incidence of frailty observed for each unit increase in AGP (OR = 3.42, 95%CI = 1.83–6.39, P < 0.001). When AGP was analyzed as a tertile variable, individuals in the highest tertile had a higher risk of frailty compared to those in the lowest tertile after adjusting for all covariates (OR = 1.78, 95%CI = 1.21–2.59, p = 0.003, P for trend = 0.002). The results of the multifactor-adjusted smoothed curve fitting plots and threshold effect analyses indicated a nonlinear relationship between AGP and frailty, with an inflection point of 1.05. In addition, ROC curve analysis showed that AGP (AUC = 0.664) had a greater diagnostic value for frailty than hsCRP (AUC = 0.656). Subgroup and interaction analyses demonstrated that none of the examined variables showed a statistically significant interaction with the association between AGP and frailty. The results of this cross-sectional study indicate a significant positive association between AGP and frailty in a population of females aged 20–49 years in the United States. However, these findings need to be further validated and extended in large-scale prospective studies.